Inhibitory Test of Gambas Fruit Extract (Luffa Acutangula L.) on Clostridium Perfringens Bacteria with Maceration Method and Fresh Extract: Uji Daya Hambat Ekstrak Buah Gambas (Luffa Acutangula L.) Pada Bakteri Clostridium Perfringens dengan Metode Maserasi dan Esktrak Segar - Makhnunah, Makhnunah; Rini, Chylen Setiyo (Universitas Muhammadiyah Sidoarjo, 2020)
Plants have many chemical constituents. Utilization of plants as an alternative treatment in overcoming food poisoning, one of which is Gambas (luffa acutangula L) which contains flavonoids so that it can kill bacteria that attack the digestive system. This research was conducted in February-May 2021 and included an experimental study that aimed to determine the potential of maceration of Gambas fruit and fresh extract in inhibiting Clostridium perfringens bacteria at various concentrations. The antibacterial activity test was carried out by maceration method and fresh extract. This antibacterial potential is indicated by the form of a clear zone around the paper disk. This study used 4 concentrations, namely 25%, 50%, 75%, 100% and Penicillin as a positive control and aquadest as a negative control. Based on the non-parametric test using the Friedman test with a sign value (α <0.05) that is 0.008 which indicates that there are significant differences at various concentrations.